Reply to the comment on: “Analysis of silicones released from household items and baby articles by direct analysis in real time-mass spectrometry” by Jürgen H. Gross. J. Am. Soc. Mass Spectrom. 26, 511-521 (2015) - Gross, Jürgen H. (Journal of the American Society for Mass Spectrometry, 2016)
ᅟ